2019
DOI: 10.29244/jitkt.v11i2.25724
|View full text |Cite
|
Sign up to set email alerts
|

FUNGSI RAWA PESISIR SEBAGAI HABITAT SIDAT TROPIS Anguilla spp. DI ESTUARI SUNGAI CIMANDIRI, SUKABUMI JAWA BARAT

Abstract: Rawa pesisir merupakan rawa pasang-surut bagian dari ekosistem estuari. Rawa pesisir di Sungai Cimandiri Kabupaten Sukabumi, Jawa Barat merupakan salah satu ekosistem estuari yang memiliki peran ekologi yang penting untuk kehidupan biota air yang menetap maupun yang bermigrasi seperti ikan sidat.  Penelitian ini bertujuan untuk mengkaji fungsi rawa pesisir, biologi populasi sidat dan faktor lingkungan yang berpengaruh terhadap populasi sidat  Penelitian dilakukan secara parsial pada  September-Oktober 2016, Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 6 publications
2
8
0
6
Order By: Relevance
“…The recruitment of glass eels on the Cimandiri River in 2018 occurred throughout the year with two peak recruitment periods. The first peak occurred in April 2018, and the second peak in August 2018 [15]. In this study, a similar pattern was seen where many glass eels were caught in March-April 2021.…”
Section: Recruitment Of Glass Eelsupporting
confidence: 83%
See 3 more Smart Citations
“…The recruitment of glass eels on the Cimandiri River in 2018 occurred throughout the year with two peak recruitment periods. The first peak occurred in April 2018, and the second peak in August 2018 [15]. In this study, a similar pattern was seen where many glass eels were caught in March-April 2021.…”
Section: Recruitment Of Glass Eelsupporting
confidence: 83%
“…(Figure 4). The results of previous studies stated similar results where three types of glass eel were found in the Cimandiri River, namely A. bicolor bicolor (90.53%), A. marmorata (4.46%), and A. nebulosa nebulosa (5.02%) with A. bicolor bicolor as the dominant species [15]. Another study also obtained the same results; the results of his research obtained glass eels of A. bicolor bicolor 71.69%, A. marmorata 21.69%, and A. nebulosa nebulosa 6.60% [10].…”
Section: Recruitment Of Glass Eelsupporting
confidence: 82%
See 2 more Smart Citations
“…Daerah potensial untuk penangkapan benih sidat terutama di barat Sumatera dan selatan Jawa yang berhadapan langsung dengan Samudera Hindia (Affandi et al 1995). Sungai Cimandiri merupakan salah satu sungai yang berpotensi sebagai habitat ikan sidat (Hakim et al 2015;Triyanto et al 2019) Terdapat 3 jenis spesies sidat yang terdapat di perairan ini yakni spesies A. bicolor, A. marmorata, serta A. nebulosa (Hakim et al 2015). Sidat memiliki gizi yang tinggi dan bernilai ekonomis tinggi, baik untuk pasar lokal maupun ekspor (Noor & Abidin 2019).…”
Section: Pendahuluanunclassified